Edukasi tentang Flour Albus pada Remaja Putri di SMAN 7 Kota Jambi - Sinulingga, Selpyani; Jayanti, Ova (Jurnal Abdimas Kesehatan (JAK), 2025)
Women in Indonesia experience vaginal discharge in 90% of cases, with 60% of these cases occurring in adolescent girls. Symptoms of vaginal discharge are also experienced by adolescent girls aged 15-24 years, at a rate of approximately 31.8%. This indicates that adolescent girls are at risk of experiencing vaginal discharge. Vaginal discharge should not be taken lightly, as delayed treatment can lead to serious complications such as infertility and ectopic pregnancy. Vaginal discharge can also be a sign or symptom of cervical cancer and gonorrhea. SMA N 7 Kota Jambi is located at Jl. KH. M. Zuhdi, Ulu Gedong, Danau Teluk, Kota Jambi. Based on an initial survey, 10 female students admitted to having experienced vaginal discharge but did not take any action for treatment or prevention and tended to ignore the issue. This may occur due to a lack of knowledge and access to information among teenage girls, hence the need for education about vaginal discharge among teenage girls. The series of community service activities was conducted from September 2023 to February 2024, while the education was conducted on February 22, 2024, targeting 22 adolescent girls aged 16-18 years. The education and counseling were provided using leaflets as a medium, and an evaluation was conducted using pre-test and post-test questionnaires. The results obtained from the activity showed an increase in the knowledge of adolescent girls about Flour Albus by 2.6. The outcomes achieved include the publication of the community service results in a community service journal indexed by Sinta